PROFITABILITAS, KEBIJAKAN DIVIDEN, DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG LISTED DI BURSA EFEK INDONESIA - Edy Sucipto; Bambang Sudiyatno (Dinamika Akuntansi Keuangan dan Perbankan, 2018)
Based on this, the research has the aim to test the effect of profitability, dividend policy, and the policy of debt to the value of companies listed on the Indonesia Stock Exchange. In this study population is all listed manufacturing companies (Go Public) at the Indonesian Stock Exchange (BEI) 2011-2013. The sample in this study are listed manufacturing companies (Go Public) at the Indonesian Stock Exchange (BEI) 2011-2013. The sampling method used in this study is judgment sampling method, which is one form of purposive sampling by sampling predetermined based on the intent of the study. Based on this can be obtained samples 36 companies. Methods of data analysis using multiple linear regression analysis. Based analyst who conducted the study concluded that profitability has a significant influence on the value of the firm's dividend policy has a significant influence on the value of companies and debt policy has no significant effect on firm value. Keywords: profitability, dividend policy, debt policy, and value of the company